Board Characteristics and Islamic Bank Performance: The Role of Size as the Moderating Variable - Evidence from Indonesia - Muhamad Umar Mai (Politeknik Negeri Bandung, 2021)
This study examines the influence of board characteristics on bank performance with bank size as the moderating variable. The study was performed on Islamic Commercial Bank (BUS, Bank Umum Syariah) in Indonesia for the period of 2010-2019. The samples were 127 BUS-year observations. They were analyzed by applying ordinary least square method and processed with Warp-PLS application. Board characteristics are served as proxy variables with board of directors size, board of directors meetings, and female board of directors while bank performance is served as proxy with Return On Asset. The result conveys that female directors in the board and board of directors meeting have positive and significant influence on Return On Asset. On the other hand, board of directors size shows an insignificant influence. The results also show that size moderates negatively the effect of board of directors as well as board of directors meeting on Return on Asset. However, it is insignificant in moderating the influence of female directors in the board over Return On Asset.